Autour d’une double origine : histoire du capitalisme racial. Entretien avec Sylvie Laurent - Igor Krtolica; Aurélia Michel; Sylvie Laurent (Tracés)
At the heart of Western history, Caribbean and African-American thinkers identified the inaugural relationship between race and capitalism early in societies where this articulation is particularly sensitive. By the end of the 18th century, racial capitalism in North America had become intertwined with the promise of democracy. From then on, the history of the Americas bears witness to the paradoxical interweaving of capitalism and racial violence on the one hand and democracy on the other. This double – or even triple – origin lies at the heart of Americanist Sylvie Laurent’s latest book, Capital et race (2024). Drawing on the central intellectual myths on which the United States, and more broadly the modern West, is founded, she focuses on the other side of the liberal emancipation narrative: the erasure of a far-reaching operation of capitalist and racial violence. This mechanism makes the modern “origin of inequality” an impossible narrative.